2019
DOI: 10.1111/1471-0528.15897
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, abdominal fatness, weight gain and the risk of urinary incontinence: a systematic review and dose–response meta‐analysis of prospective studies

Abstract: Background Adiposity has been associated with elevated risk of urinary incontinence in epidemiological studies; however, the strength of the association has differed between studies.Objectives To conduct a systematic literature review and doseresponse meta-analysis of prospective studies on adiposity and risk of urinary incontinence.Search strategy We searched PubMed and Embase databases up to 19 July 2017.Selection criteria Prospective cohort studies were included.Data collection and analysis Data were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 70 publications
(125 reference statements)
2
27
0
Order By: Relevance
“…Based on this limited evidence there are signs that weight loss interventions may be considered as an option for a lifestyle treatment due to some signs of effectiveness to improve symptoms in UI, prevalence of weekly UI and there being limited adverse events. Previous systematic reviews have shown a positive association with increased BMI and risk of UI (Aune et al 2019;Lamerton et al 2018).…”
Section: Commentarymentioning
confidence: 80%
See 1 more Smart Citation
“…Based on this limited evidence there are signs that weight loss interventions may be considered as an option for a lifestyle treatment due to some signs of effectiveness to improve symptoms in UI, prevalence of weekly UI and there being limited adverse events. Previous systematic reviews have shown a positive association with increased BMI and risk of UI (Aune et al 2019;Lamerton et al 2018).…”
Section: Commentarymentioning
confidence: 80%
“…This condition can have a significant clinical (Yang et al 2018), psychological (Farage et al 2008;Sims et al 2011), and financial impact (Thom et al 2010) on an individual's life. The risk of developing UI is associated with several non-modifiable modifiable risk factors of age (Milsom and Gyhagen 2019), gender (Nitti 2001) and family history (von Gontard et al 2011) and modifiable risk factors of weight (Aune et al 2019), smoking (Kawahara et al 2020), diet (Maserejian et al 2010) and caffeine intake (Gleason et al 2013). Despite the association with such modifiable risk factors, there is limited evidence supporting interventions which aim to affect their influence (Imamura et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was found that the lumbar disc herniation increased the frequency of obesity exclusively for women in various regression models by 1,156 and 1,229 times. Studies are indicating that the prevalence of urinary incontinence increases in parallel with the increase in BMI value [41][42]. In some cases, the disease increases the risk of obesity, while in other cases, obesity increases the risk of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Women with a body mass index (BMI) > 30 kg/m 2 should be advised to lose weight as increased BMI has an almost linear association with UI. 14 Smoking cessation should be encouraged as a large population-based study found that smoking was associated with UI. 15…”
Section: Overactive Bladder and Urgencymentioning
confidence: 99%